N-Aryl Benzimidazole and Benzotriazole Derivatives and Their Hybrids as Cytotoxic Agents: Design, Synthesis and Structure–Activity Relationship Studies - Yulia R. Aleksandrova; Natalia S. Nikolaeva; Inna A. Shagina; Karina D. Smirnova; Alla A. Zubishina; Alexander I. Khlopotinin; Artem N. Fakhrutdinov; Alexander L. Khokhlov; Roman S. Begunov; Margarita E. Neganova (Molecules)
The era of chemotherapy began in the 1940s, which is the basis of traditional antitumor approaches and, being one of the most high-tech treatment methods, is still widely used to treat various types of cancer. A promising direction in modern medicinal chemistry is currently the creation of hybrid molecules containing several pharmacophore fragments of different structures. This strategy is successfully used to increase the therapeutic efficacy of cytotoxic agents and reduce side effects. In this work, we synthesized 10 1-aryl derivatives of benzimidazole and benzotriazole and 11 hybrids based on them. Among the compounds obtained, the most promising hybrid molecules were diphenylamines, containing an amino group and a benzotriazole cycle in the ortho position to the bridging NH group, which showed significant cytotoxic activity, excellent antioxidant properties and the ability to suppress the migration activity of tumor cells. Taken together, our results demonstrate that substituted diphenylamine-based bipharmacophoric compounds may serve as a promising platform for further optimization to obtain effective antitumor compounds.